The Structural Model of Problems and Prioritized Programs to Develop Village Enterprises in Jambi Province - Asnelly Ridha Daulay; Rialdi Syaputra (The Indonesian Journal of Planning and Development, 2019)
The number of village enterprises in Jambi Province until 2017 was only 320 of 1,551 villages. Need more village enterprises to be established in order to increase the economic independence of rural areas and their community. However, that is not easy since many existing village enterprises currently experience some difficulties. This study aims to analyze problems faced by village enterprises and programs prioritized to overcome the problems. The research conducted in three different locations that represent western part of Jambi, middle and eastern part of Jambi. Each of them had different core businesses, namely Dusun Dalam of Kerinci Regency (core business in processing of agricultural products), Lubuk Beringin of Bungo Regency (core business is tourism village), and Dataran Kempas of Tanjung Jabung Barat Regency (core business is the production of compost). Data collected by doing observation and focus group discussion and then analyzed by using Interpretative Structural Model (ISM). This study reveals that the main problems concerned with human resources even though they are expressed by stakeholders in each village enterprise with different narratives. Issues concerning capital also arise, but they are not in the top position of all problems faced. The programs they put in priorities are some training in area of leadership, accountancy, marketing, entrepreneurship and others that related to the development of human resources.